Revision der von Ferdinand Rudow beschriebenen Ichneumonidae. II: Pezolochus Förster und Pezomachus Gravenhorst (Hymenoptera, Ichneumonidae). - Schwarz, Martin; Horstmann, Klaus (Contributions to Entomology = Beiträge zur Entomologie, 1993)
Ferdinand Rudow (1914 and 1917) described 67 species in the genera Pezolochus Förster and Pezomachus Gravenhorst (Ichneumonidae, Hymenoptera). Most of them are from the Western Palearctic Region, four taxa are Nearctic (Pezomachus caudatus, Pezomachus dimidiativentris, Pezomachus longipes, Pezomachus melanofthalmus). With the exception of three Nearctic species all taxa are revised here. The types of four species could not be found. One of these is interpreted after the original description, and the other three names are still nomina dubia. 18 names are preoccupied, and one name (Pezomachus monozonius) is possibly preoccupied. 57 lectotpyes are designated, and altogether 57 new synonyms are indicated. Only two names given by Rudow (Pezomachus haemorhoidalis, Pezomachus rificeps) are considered to be valid names for known species. Nomenclatural Actshaemorhoidalis (Rudow, 1917) (Gelis), Lectotype described as Pezomachus haemorhoidalisruficeps (Rudow, 1914) (Gelis), comb. n. hitherto Pezomachus ruficepsobvia Ceballos, 1925 (Gelis (Thaumatotypidea)), syn. n. of Gedlis haemorrhoidalis (Rudow, 1917)gracilis Rudow, 1917 (Pezolochus), Lectotype; syn. n. of Gelis ruficornis (Retzius, 1783)longicauda Rudow, 1914 (Pezolochus), Lectotype; syn. n. of Gelis ruficornis (Retzius, 1783)albulae Rudow, 1917 (Pezomachus), Lectotype; syn. n. of Gelis agilis (Fabricius, 1775)alpinus Rudow, 1917 (Pezomachus), Lectotype; syn. n. of Gelis cursitans (Fabricius, 1775)aphidicola Rudow, 1917 (Pezomachus), Lectotype; syn. n. of Gelis bicolor (Villers, 1789)aphidum Rudow, 1917 (Pezomachus), syn. n. of Gelis rufogaster Thunberg, 1827araneicola Rudow, 1914 (Pezomachus), Lectotype; syn. n. of Gelis rufogaster Thunberg, 1827araneicolus Rudow, 1917 (Pezomachus), Lectotype; syn. n. of Pezomachus ? rufogaster Thunberg, 1827araneivorus Rudow, 1914 (Pezomachus), Lectotype; syn. n. of Gelis longulus (Zetterstedt, 1838)balteatus Rudow, 1917 (Pezomachus), Lectotype; syn. n. of Gelis rufogaster Thunberg, 1827bicolorinus Rudow, 1917 (Pezomachus), Lectotype; syn. n. of Gelis ruficornis (Retzius, 1783)borealis Rudow, 1917 (Pezomachus), Lectotype; syn. n. of Gelis corruptor (Förster, 1850)braconidum Rudow, 1917 (Pezomachus), Lectotype; syn. n. of Gelis cursitans (Fabricius, 1775)clythrae Rudow, 1917 (Pezomachus), syn. n. of Aptesis nigrocincta (Gravenhorst, 1815)coccivorus Rudow, 1917 (Pezomachus), Lectotype; syn. n. of Gelis notabilis (Förster, 1850)collaris Rudow, 1917 (Pezomachus), Lectotype; syn. n. of Gelis vagans (Olivier, 1792)cruentatus Rudow, 1917 (Pezomachus), Lectotype; syn. n. of Gelis acarorum (Linnaeus, 1758)cruentus Rudow, 1917 (Pezomachus), Lectotype; syn. n. of Gelis longulus (Zetterstedt, 1838)cuculliae Rudow, 1917 (Pezomachus), Lectotype; syn. n. of Gelis agilis (Fabricius, 1775)ephippium Rudow, 1914 (Pezomachus), Lectotype; syn. n. of Gelis meigenii (Förster, 1850)eupitheciae Rudow, 1917 (Pezomachus), Lectotype; syn. n. of Gelis agilis (Fabricius, 1775)exareolatus Rudow, 1917 (Pezomachus), Ledctotype; syn. n. of Gelis vagans (Olivier, 1792)flavipes Rudow, 1917 (Pezomachus), Lectotype; syn. n. of Gelis ruficornis (Retzius, 1783)formicarius Rudow, 1917 (Pezomachus), Lectotype; syn. n. ? of Gelis ? bicolor (Villers, 1789)fulvicornis Rudow, 1917 (Pezomachus), Lectotype; syn. n. of Gelis acarorum (Linnaeus, 1758)globulus Rudow, 1917 (Pezomachus), Lectotype; syn. n. of Gelis femoralis (Brischke, 1881)graecus Rudow, 1917 (Pezomachus), Lectotype; syn. n. of Gelis lichtensteini (Pfankuch, 1913)helicis Rudow, 1917 (Pezomachus), Lectotype; syn. n. of Gelis cursitans (Fabricius, 1775)hercyniae Rudow, 1917 (Pezomachus), Lectotype; syn. n. of Gelis melanocephalus (Schrank, 1781)intrans Rudow, 1917 (Pezomachus), Lectotype; syn. n. of Gelis agilis (Fabricius, 1775)isabellinus Rudow, 1917 (Pezomachus), Lectotype; syn. n. of Gelis rufogaster Thunberg, 1827lineatus Rudow, 1917 (Pezomachus), Lectotype; syn. n. of Gelis agilis (Fabricius, 1775)melanofthalmus Rudow, 1917 (Pezomachus), Lectotype; syn. n. of Gelis venatorius (Förster, 1850)mezozonius Rudow, 1917 (Pezomachus), Lectotype; syn. n. of Gelis rotundiventris (Förster, 1850)microrum Rudow, 1917 (Pezomachus), Lectotype; syn. n. of Gelis agilis (Fabricius, 1775)minimus Rudow, 1917 (Pezomachus), Lectotype; syn. n. of Gelis ruficornis (Retzius, 1783)monozonicus Rudow, 1917 (Pezomachus), Lectotype; syn. n. of Gelis agilis (Fabricius, 1775)nigerrimus Rudow, 1917 (Pezomachus), Lectotype; syn. n. of Gelis agilis (Fabricius, 1775)nigrocinctus Rudow, 1917 (Pezomachus), Lectotype; nom. praeocc. of Aptesis nigrocincta (Gravenhorst, 1815)pemphigicola Rudow, 1917 (Pezomachus), Lectotype; syn. n. of Gelis rufogaster Thunberg, 1827pieridis Rudow, 1917 (Pezomachus), Lectotype; syn. n. of Gelis rufogaster Thunberg, 1827pilosellus Rudow, 1917 (Pezomachus), Lectotype; syn. n. of Theroscopus pedestris (Fabricius, 1775)potentillae Rudow, 1917 (Pezomachus), Lectotype; syn. n. of Gedlis vagans (Olivier, 1792)psychidum Rudow, 1917 (Pezomachus), Lectotype; syn. n. of Gelis vagans (Olivier, 1792)psychivorus Rudow, 1917 (Pezomachus), Lectotype; syn. n. of Gelis cursitans (Fabricius, 1775)retiniae Rudow, 1917 (Pezomachus), Lectotype; syn. n. of Gelis corruptor (Förster, 1850)rosarum Rudow, 1917 (Pezomachus), Lectotype; syn. n. of Gelis agilis (Fabricius, 1775)rufipes Rudow, 1917 (Pezomachus), Lectotype; syn. n. of Gelis semirufus (de Stefani, 1884)rufostictus Rudow, 1917 (Pezomachus), Lectotype; syn. n. of Gelis agilis (Fabricius, 1775)selandriae Rudow, 1917 (Pezomachus), Lectotype; syn. n. of Theroscopus trifasciatus Förster, 1850siculus Rudow, 1917 (Pezomachus), Lectotype; syn. n. of Gelis lichtensteini (Pfankuch, 1913)ulmicola Rudow, 1917 (Pezomachus), Lectotype; syn. n. of Gelis rufogaster Thunberg, 1827unicinctus Rudow, 1917 (Pezomachus), Lectotype; syn. n. of Gewlis acarorum (Linnaeus, 1758)vanessae Rudow, 1917 (Pezomachus), Lectotype; syn. n. of Gelis agilis (Fabricius, 1775)verrucosus Rudow, 1917 (Pezomachus), Lectotype; syn. n. of Gelis formicarius (Linnaeus, 1758)versicolor Rudow, 1917 (Pezomachus), Lectotype; syn. n. of Gelis corruptor (Förster, 1850)violaceus Rudow, 1917 (Pezomachus), Lectotype; syn. n. of Gelis cyanurus (Förster, 1850)